Association of Educational Attainment With Adiposity, Type 2 Diabetes, and Coronary Artery Diseases: A Mendelian Randomization Study - Cao, Min; Cui, Bin (Frontiers in Public Health, 2020)
Background: Observational studies showed that educational attainment (EA) is associated with cardiometabolic diseases, but the long interval between exposure and outcome makes it difficult to infer causality. We herein used Mendelian randomization (MR) to examine the causal effects of EA on adiposity, type 2 diabetes (T2D), and coronary artery disease (CAD). Methods: A two-sample MR analysis was conducted using genome-wide association study (GWAS) summary statistics. Seventy-four instrumental variables (IVs) were used to determine the causal effect of EA on cardiometabolic diseases. Sensitivity analyses were also performed to detect the pleiotropy of the IVs. Results: Using the MR approach, we found that each additional year in EA is associated with a reduction in the body mass index (BMI) (β −0.17 [95% CI −0.23, −0.10], P = 8.85 × 10−7), a 39% reduction in the odds of having T2D (OR 0.61 [95% CI 0.50, 0.75], P = 1.16 × 10−6), and a 36% reduction in the odds of having CAD (OR 0.64 [95% CI 0.55, 0.75], P = 2.38 × 10−8) at the Bonferroni-adjusted level of significance. Conclusion: Our findings suggest a causal role of EA on the cardiometabolic diseases including adiposity, T2D, and CAD.